Eksistensi Syafaat di Akhirat (Studi Pemikiran Teologi Ahlu Al-Sunnah) (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2022)
Intercession is one issue that is often debated among scholars. In this regard, this research is motivated by the fact that in the literature there is a distinction (difference) of opinion regarding intercession in the hereafter that occurs between the theological schools of ahlus sunnah and also influences interpretation, among them represented by Fakhruddin al-Razi and al- Zamakhsyari. The approach method used in this study is the muqaran method (comparison). In simple terms, this research is directed to look at the things that make the scholars differ in their opinion in acknowledging the existence of intercession in the hereafter. As a result of the discussions presented in this study, the authors come to the conclusion that in discussing the term intercession among the theological schools of ahlus sunnah there are differences. First, in the view of Asy'ariyah, everyone except infidels is guaranteed to get intercession on the Day of Resurrection. Second, in the view of Muktazilah, everyone will get intercession on the Day of Resurrection except for disbelievers and those who commit major sins. Third, in the view of the Salafiyah, intercession is included in the problem of mutasyabihat, there is no need to interpret it because intercession is a privilege given by Allah to whoever He wills, only Allah knows its essence. The difference between the theological schools of ahlus sunnah in interpreting the theme of intercession can be seen in the emphasis of both. If Asy'ariyah seems to recognize all believers without the slightest exception, then Muktazilah excludes intercession for every believer who commits a grave sin. In the end one's understanding of intercession will have implications for the affiliation of the theological school one adheres to. If someone denies intercession for a believer who has committed a grave sin, then it is certain that he adheres to the Muktazilah theological beliefs. But if recognizing that all believers get intercession, then their affiliation is to Ash'ariyah theology.